Teacher-Student-Relationship Quality in Inclusive Secondary Schools: Theory and Measurement of Emotional Aspects of Teaching - Pastore, Giuliana; Luder, Reto (Frontiers in Education, 2021)
Inclusive healthy schools are committed to provide a learning environment for a healthy develop-ment and optimal learning support for all students, regardless of their performance, language, learn-ing and behavior disposition or disability. In order to achieve this goal, the relationship between teacher and students is crucial. Research in this area has shown the importance of emotional aspects as a mark of quality of teacher-student relationships, recognizing them as strong predictors for better achievement, compared to professional and subject-related didactic aspects of teaching. Neverthe-less, empirical studies in inclusive schools are seldom considering teacher-student relationships, as a theoretically sound conceptualization in the context of research in inclusive schools is missing. In the present paper, based on the attachment theory and the research on joint attention, two emotional components of teacher-student relationships are examined as key-concepts of high relevance for inclusive schools (emotional resonance and shared intentionality). It is also discussed how to empir-ically operationalize and measure these emotional components with the intention of analyzing the current situation of inclusive schools in future studies.